Analysis of the Translation of Arabic Texts in the Book of Science: Balaghah Tarjamah Jauhar Maknun by Imam Akhdlori - Gema Mutakabbir; Rinaldi Supriadi; Nunung Nursyamsiah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2023)
Arabic texts can be understood in their meaning through the process of translation which require specific techniques. Translation techniques will offer resolutions to the translation difficulties encountered by translators. The purpose of this research is to describe the translation techniques from Arabic to Indonesian in the book